2004
DOI: 10.1542/peds.114.1.e74
|View full text |Cite
|
Sign up to set email alerts
|

Conscious Sedation of Children With Propofol Is Anything but Conscious

Abstract: ABSTRACT. Objective. To determine the depth of sedation required for bone marrow aspiration and intrathecal injection of chemotherapeutic agents in children using a bispectral (BIS) index monitor and clinical assessment by an independent observer.Methods. Sixteen children who were undergoing 19 intrathecal chemotherapy and bone marrow aspirations were enrolled in the study. Their ages ranged from 23 months to 190 months with a mean of 79 months. The BIS index was recorded every 5 minutes by an independent obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 15 publications
1
22
0
2
Order By: Relevance
“…Otherwise, forced pressure on children related to the procedure will cause pain and nervousness for the patients and the relatives, which are not good for the treatment. Furthermore, it is useless to console the children after the procedure (Reeves et al, 2004;Lundeberg and Roelofse, 2011;Masala et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, forced pressure on children related to the procedure will cause pain and nervousness for the patients and the relatives, which are not good for the treatment. Furthermore, it is useless to console the children after the procedure (Reeves et al, 2004;Lundeberg and Roelofse, 2011;Masala et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous studies, our data showed that propofol causes hypotension and might lead to hypoventilation or airway obstruction. [30][31][32][33][34] It should be therefore used only by experienced pediatric intensivists or anesthetists. The propofol infusion syndrome, a fatal combination of renal and cardiac failure, rhabdomyolysis, and acidosis, is related to a long-term propofol sedation of more than 48 hours, so patients should not be at risk when propofol is used for short-term procedural sedation.…”
Section: Discussionmentioning
confidence: 99%
“…431 Several sedation studies have examined the utility of this device and degree of correlation with standard sedation scales. 347,363,[432][433][434][435] It appears that there is some correlation with BIS values in moderate sedation, but there is not a reliable ability to distinguish between deep sedation and moderate sedation or deep sedation from general anesthesia. 432 Presently, it would appear that BIS monitoring might provide useful information only when used for sedation with propofol 363 ; in general, it is still considered a research tool and not recommended for routine use.…”
Section: Processed Eeg (Bispectral Index)mentioning
confidence: 99%